A simple segmentation approach for unconstrained cursive handwritten words in conjunction with neural network - Khan, Amjad Rehman; Mohamad, Dzulkifli (CSC Journals, Kuala Lumpur, Malaysia, 2008)

(untitled)
This paper presents a new, simple and fast approach for character segmentation of unconstrained handwritten words. The developed segmentation algorithm over-segments in some cases due to the inherent nature of the cursive words. However the over segmentation is minimum. To increase the efficiency of the algorithm an Artificial Neural Network is trained with significant amount of valid segmentation points for cursive words manually. Trained neural network extracts incorrect segmented points efficiently with high speed. For fair comparison benchmark database IAM is used. The experimental results are encouraging